Discriminant analysis of normal and malignant breast tissue based upon INAA investigation of elemental concentration - Ng, K.H.; Ong, S.H.; Bradley, D.A.; Looi, L.M. (Faculty of Medicine, University of Malaya, 1996)
Discriminant analysis of six trace element concentrations measured by instrumental neutron activation analysis (INAA) in 26 paired-samples of malignant and histologically normal human breast tissues shows the technique to be a potentially valuable clinical tool for making malignant-normal classification. Nonparametric discriminant analysis is performed for the data obtained. Linear and quadratic discriminant analyses are also carried out for comparison. For this data set a formal analysis shows that the elements which may be useful in distinguishing between malignant and normal tissues are Ca, Rb and Br, providing correct classification for 24 out of 26 normal samples and 22 out of 26 malignant samples.